FEA modelling of stress distributions in concrete test specimens compressed through rubber sheets - Ismail Ismaliza; Gough Julia (Journal of Rubber Research, 2012)
A finite element (FE) study of the behaviour of concrete blocks compressed against rubber sheets was conducted. The results were compared to experimental tests of the same assembly reported in literature. It was found that tensile stresses developed within the concrete due to non-uniform compression of the rubber and were likely to have been the cause of failure of the concrete except where the rubber sheet was very thin or absent. The effect disappeared if contact between the rubber and concrete was frictionless.
Source Year: 2012
Keywords: Compression; Concrete; FEA; Stress